KONSEP MODERASI BERAGAMA DALAM TAFSIR TARBAWI QS. AL-BAQARAH:62 - NOVA FASADENA; Nurul Huda; Zainul Hasan; Nur Cholid (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2023)
Maraknya aksi radikalisme berujung terorisme membuat Indonesia menjadi darurat moderasi beragama. Ayat-ayat moderasi beragama terus dikampanyekan dalam mata pelajaran PAI untuk memahamkan remaja awam agar tidak mudah direkrut menjadi anggota Islam radikal. Salah satu ayat yang urgen untuk dibahas adalah QS. Al-Baqarah:62 karena isi ayat itu yang memposisikan orang beriman sama dengan umat agama lainnya. Untuk itu perlu bagi kita menyelami makna ayat tersebut dalam perspektif mufassir klasik dan modern. Tulisan ini bertujuan untuk mendeskripsikan pandangan mufassir klasik dan modern terhadap QS. Al-Baqarah:62. Metode penelitian yang digunakan adalah pendekatan kualitatif dengan jenis kajian Pustaka. Sumber data primer adalah QS. Al-Baqarah:62 dan tafsir Al-Quran Klasik (Jalalain, Ibnu Kastir, Al-Qurthubi, At-Thabari) serta tafsir Al-Quran modern (Al-Mishbah, Al-Azhar, Tafsir fi Zhilalil Quran, dan Departemen Agama RI). Analisis data menggunakan teknik pengumpulan data, kondensasi data, penyajian data, dan verifikasi data. Hasil penelitian menunjukkan mufassir klasik dan modern memaknai konsep moderasi beragama dalam konteks orang beriman, Yahudi, Nasrani, dan Sabi’in sebagai berikut (1) Islam menganggap sama umatnya yang mau kembali. (2) Bagi yang tidak mau beriman maka tidak ada paksaan. (3) Allah mengganjar makhluknya sesuai dengan amalnya. (4) Mufassir klasik dan mufassir modern tidak banyak perbedaan yang Nampak kecuali pemahaman keempat umat tersebut apakah ayat tersebut tertuju untuk konteks saat ini atau zaman nabi. The rise of acts of radicalism that lead to terrorism has made Indonesia an emergency moderation of religion. Religious moderation verses continue to be campaigned in PAI subjects to make ordinary youth understand that they are not easily recruited to become members of radical Islam. One verse that is urgent to discuss is QS. Al-Baqarah: 62 because the contents of the verse position believers the same as people of other religions. For this reason, it is necessary for us to explore the meaning of the verse from the perspective of classical and modern commentators. This paper aims to describe the views of classical and modern commentators on QS. Al-Baqarah: 62. The research method used is a qualitative approach to the type of literature review. Primary data source is QS. Al-Baqarah: 62 and the interpretation of the Classical Al-Quran (Jalalain, Ibnu Kastir, Al-Qurthubi, At-Thabari) as well as modern interpretations of the Al-Quran (Al-Mishbah, Al-Azhar, Tafsir fi Zhilalil Quran, and the Ministry of Religion of the Republic of Indonesia). Data analysis uses techniques of data collection, data condensation, data presentation, and data verification. The results of the study show that classical and modern mufassir interpret the concept of religious moderation in the context of believers, Jews, Christians, and Sabians: (1) Islam considers the same people who want to return. (2) For those who don't want to believe, there is no compulsion. (3) Allah rewards his creatures according to their deeds. (4) Classical commentators and modern commentators do not see much difference except for the understanding of the four ummahs whether for the current context or the time of the prophet. Keywords: religious moderation, QS. al-baqarah:62, tarbawi interpretation.